Lesson plan enhancement and development of pupil constructed response skill in science - Tan, Maria Luz Maramion (2006)
This study was undertaken to determine the pupils' difficulties in answering constructed response items and the effect of the Enhanced Lesson Plans on the achievement of Grade 6 pupils in Science. The Enhanced Lesson Plan features several activities designed for each constructed response skill. Sixty Grade 6 pupils of KTMSCES, Davao City were divided to two groups to test the lesson plan. The effectiveness was evaluated using the Constructed Response Science Achievement Test and Interview Guide. The results revealed that the group exposed to enhanced lesson plans had significantly higher mean score in the Constructed Response Science Achievement Test than the group without enhanced lesson plans. The enhanced lesson plans are helpful in improving students' constructed response skill in science.